Piknik - Rafaelová, Kateřina (Vysoké učení technické v Brně. Fakulta výtvarných umění)
Cílem mé práce je komunikace s divákem prostřednictvím simplicity v malířském médiu na pozadí rodinných vztahů. Prostřednictvím banalizovaných motivů nechávám diváka pozastavit se nad vlastní hodnotou rodinného sdílení.

The final work aims to communicate via simplicity in painting's form related to family background. Trough the banalized motives I'm letting the spectator to stop for a while and think about the values of family sharing.
Picnic
Keywords: rodina; zázemí; sdílení; malba; malířské formy; simplicita; hodnoty; vazby; rodinné vztahy; family; background; sharing; painting; painting's form; simplicity; values; ties; family relationships